Analysis Study of Endurance and Agility Levels During the Covid-19 Pandemic of Students At Bintang Muda Wolo Football Academy in Penawangan District - Wigiyantoro, Toto; Anam, Khoiril (Universitas Negeri Semarang, 2022)
The endurance and agility of soccer in a soccer player are factors in supporting the game of soccer. Increasing endurance and agility can be done by training according to a predetermined program. However, since the Covid-19 pandemic, training is only done once a week and not even once a week. This can affect the endurance and agility of players. Based on the research problems, they are: 1) What is the endurance condition of the students of football school Bintang Muda Wolo (BMW) during the covid 19 pandemic? 2) How is the agility level of the football school Wolo Bintang Muda (BMW) during the covid 19 pandemic? This type of research is descriptive research. The research method uses a survey method with data collection techniques in the form of tests and measurements. The population is 42 students of SSB Bintang Muda Wolo, aged 13-15 in 2021. Sampling uses a purposive sampling technique with a sample of 15 students. The instrument used is an agility test using the Illinois agility run test and an endurance level test using a 1000 m run test. The results of the research and analysis showed that the level of endurance was 0% in the very good category, 2 students or 13% in the good category, 6 students or 40% in the sufficient category, 5 students or 33% in the poor category, and 2 or 13% in the very poor category. And the agility level is 0% in the very good category, 4 students or 27% in good condition, 7 students or 47% in the sufficient category, 1 student or 7% in poor condition, and 3 students or 20% of them in very poor condition. The conclusion in this study is that the level of endurance and agility of SSB Bintang Muda Wolo students is sufficient. Therefore, coaches must be able to improve their abilities despite the COVID-19 pandemic by controlling online training.